Upregulation of the Endosomal-Lysosomal Pathway in the Trembler-J Neuropathy - Notterpek, Lucia (J Neurosci, 1997)
A nonconservative leucine to proline mutation in peripheral myelin protein 22 (PMP22) causes the Trembler-J (Tr(J)) neuropathy in mice and humans. The expression levels and localization of the PMP22 protein in the Tr(J) mouse have not been previously determined. The aim of our studies was to reevaluate the extent of myelin deficit in genotyped heterozygous and homozygous animals and to examine how the Tr(J) mutation alters the normal in vivo post-translational processing of PMP22. Morphological studies show evidence for primary dysmyelination and myelin instability in affected animals. As expected, Western blot analysis indicates that in adult heterozygousTr(J) animals, the level of PMP22 is markedly decreased, similar to myelin basic protein and protein zero, whereas myelin-associated glycoprotein is largely unaffected. The decrease in myelin protein expression is associated with an increase in lysosomal biogenesis, suggestive of augmented endocytosis or autophagy. Double-immunolabeling experiments show the accumulation of PMP22 in endosomal/lysosomal structures of Tr(J)Schwann cells, and chloroquine treatment of nerve segments indicates that the degradation of protein zero, PMP22, and myelin basic protein is augmented in Tr(J) nerves. These studies suggest that the Tr(J)mutation alters myelin stability and that the mutant protein is likely degraded via the lysosomal pathway.